A FDTD SURFACE IMPEDANCE BOUNDARY CONDITION USING Z-TRANSFORMS - Beggs, John H. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The surface-impedance boundary condition for the Finite-Difference, Time-Domain (FDTD) method is re-formulated using digital filtering theory and Z trans-forms. The approach expands upon recent work in de-veloping an efficient surface-impedance boundary condi-tion for FDTD. The present work involves formulating the surface-impedance boundary condition in the frequency domain for a lossy dielectric half-space and for a thin lossy dielectric layer backed by a perfect conductor. The impedance function of the lossy medium is approximated with a series of low-pass filters. This approximation is independent of material properties and these low-pass fil-ters are converted to corresponding digital filters using Z-transform theory. The FDTD surface-impedance bound-ary condition is reformulated in the Z domain, and the corresponding time-domain electric field sequence updat-ing equation involves a recursive formula. Results are presented for both one and two-dimensional test prob-lems.